Analysis of Determinants of Regional Economic Growth on the East Coast of North Sumatra - Dahliana Saragih (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2021)
The purpose of this research is to analyze the determinant of economic growth regional East Coast of North Sumatra in five years. The location of this research is 4 regencies and 4 cities which are in some area of ​​the East Coast of North Sumatra. The independent variable in this The number of Working population and Human Development Index (HDI). The methods we use in this research is descriptive quantitative with applying for secondary data which is based on central of statistics (BPS) North Sumatra 2011-2015. To see the influence of the total inhabitant which work and human development index for economic growth use analysis Regression panel data. this data will be estimation with equalization model Random Effect Model (REM) use application tool of computer program E-Views. According to approximate estimation result.